Clinical Education Status According to the Nursing and Midwifery Students Point of View Tehran University of Medical Sciences - Shahram Baraz Pordanjani; Malek Fereidooni Moghadam; Mohamadreza Loorizade (Kerman University of Medical Sciences, 2009)
Background & Objective : Promoting quality of clinical education necessitates continuous evaluation of the current situations identifying strengths and improving weaknesses This study was designed to assess clinical education status according to the nursing and midwifery students point of view in Tehran University of Medical Sciences Methods : In this descriptive study which was conducted in 20045 all senior nursing students who were doing a Bachelor of Science and senior midwifery students who were doing technicians Course (250 students) were asked to complete a 36 item questionnaire in a selfadministered way Results : The most important strengths of clinical education (according to mean scores) were "on time presence of the student in the ward" (8906) then "on time presence of the instructor in the ward" (8505) "considering the prerequisite clerkship courses" (825) "proper instructors behavior with students" (741) "clinical instructors interest in working" (7392) and "instructors clinical track record" (731) The most significant weaknesses of clinical education were related to "use of audiovisual aids in clinical atmosphere" (984) "enough number of students in the ward" (1491) and "having facilities" (1968) Conclusion : Although some aspects of clinical education were good and excellent improving positive aspects and modifying the weaknesses may be an effective step in promoting quality of clinical education Repetitive assessments of clinical fields and comparing the current situation with the previous or next ones can reveal the strengths and weaknesses of clinical education